Why Do Patients Seek Diagnose Dis-accordance With Hierarchical Medical System Related Policies in Tertiary Hospitals? A Qualitative Study in Shanghai From the Perspective of Physicians - Yuhui Ruan; Yuhui Ruan; Yuhui Ruan; Yuhui Ruan; Jin Luo; Jin Luo; Hong Lin; Hong Lin (Frontiers Media S.A., 2022)
BackgroundAlthough the Hierarchical Medical System has been utilized in China for many years, it is inadequate for guiding patients in adopting appropriate diagnose-seeking behaviors in accordance with related policies. This study examined how patients' diagnose-seeking behavior in tertiary hospitals that is dis-accordance with Hierarchical Medical System related policy ("DSB-dis-accordance") arise and ways to guide patients away from such behaviors, both from the perspective of physicians.MethodsA qualitative study based on a mixed method including in-depth interviews and grounded theory. Twenty-seven physicians with more than 2 years of experience serving in tertiary hospitals of Shanghai were involved after reviewing the related purposes and requirements. Patients' "DSB-dis-accordance" was studied from the perspective of physicians.ResultsPatient-related factors (habits, trust, and knowledge), physician-related factors (conservative preference, risk avoidance), and system-related factors (accessibility, operability) affected patients' diagnose-seeking behavior.ConclusionsPatient-related, physician-related, and system-related factors affecting patients' diagnose-seeking behaviors in tertiary hospitals should be addressed by investing more health resources in lower-level hospitals, enhancing dissemination of health-related and policy-related knowledge, refining the classification of diseases, incentivizing physicians, and developing appropriate follow-up measures. Physicians could then become more involved in guiding patients' "DSB-dis-accordance," thereby benefitting development of the Hierarchical Medical System in China.